Guide to Selected Bioinformatics Internet Resources. - Christy Hightower (Issues in Science and Technology Librarianship)
This guide provides a list of bioinformatics resources on the Internet. Because of the potential for this field to sweep a great deal of both computer science and molecular biology under its wing, this guide is by necessity very selective rather than comprehensive. There is a focus on human rather than plant or animal data sources and the ethical, business, political and legal aspects of bioinformatics and genomics are completely ignored (except for their appearance in the news sites). The resources selected are aimed at the college and research level.